2020
DOI: 10.1128/aem.01808-20
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Efficacy and Mode of Action of Ethylzingerone [4-(3-Ethoxy-4-Hydroxyphenyl) Butan-2-One] as an Active Agent against Burkholderia Bacteria

Abstract: Burkholderia cepacia complex (Bcc) bacteria are intrinsically antimicrobial resistant opportunistic pathogens and key risk species in the contamination of non-food industrial products. New agents and formulations to prevent growth of Burkholderia in home care (cleaning agents) and personal care (cosmetics and toiletries) products are required. We characterised how ethylzingerone [4-(3-ethoxy-4-hydroxyphenyl) butan-2-one)] (HEPB) acts as a preservative with activity against Burkholderia species encountered in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In addition, EZ has shown very significant activity against problematic bacteria such as Burkholderia spp., killing them via a multifactorial mode of action which involves intracellular oxidation [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, EZ has shown very significant activity against problematic bacteria such as Burkholderia spp., killing them via a multifactorial mode of action which involves intracellular oxidation [37].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent analyses have revealed that C. albicans phenotypic and transcriptomic responses to EZ treatment were distinguishable from those of two widely used preservatives, triclosan and methylparaben. Chemogenomic analyses have demonstrated that EZ antifungal activity strongly interfered with the biosynthesis of aromatic amino acids [36,37].…”
Section: Strong Potential Of An Ethylated Analogue Of Zingerone (Ez) ...mentioning
confidence: 99%